Enhanced Metabolic Stress Augments Ischemic Preconditioning for Exercise Performance - Slysz, Joshua T.; Burr, Jamie F. (Frontiers in Physiology, 2018)
Purpose: To identify the combined effect of increasing tissue level oxygen consumption and metabolite accumulation on the ergogenic efficacy of IPC during both maximal aerobic and maximal anaerobic exercise. Methods: Twelve healthy males (22±2 years, 179±2 cm, 80±10 kg, 47.7±4 ml.kg-1.min-1) underwent four experimental conditions: i) no IPC control, ii) traditional IPC, iii) IPC with EMS and iv) IPC with treadmill walking. IPC involved bilateral leg occlusion at 220mmHg for five minutes, repeated three times, separated by 5 minutes of reperfusion. Within 10 minutes following the IPC procedures, a 30s Wingate test and subsequent (after 25-minute rest) incremental maximal aerobic test were performed on a cycle ergometer. Results: There was no statistical difference in anaerobic peak power between the no IPC control (1211±290W), traditional IPC (1209±300W), IPC + EMS (1206±311W), and IPC + Walk (1220±288W; P=0.7); nor did VO2max change between no IPC control (47.7±2ml.kg-1.min-1), traditional IPC (48.4±6 ml.kg-1.min-1), IPC + EMS (49.1±4 ml.kg-1.min-1) and IPC + Walk (48.0±6 ml.kg-1.min-1; P=0.3). However, the maximal watts during the VO2max increased when IPC was combined with both EMS (304±38W) and walking (308±40W) compared to traditional IPC (296±39W) and no IPC control (293±48W; P=0.02). Conclusion: This study shows that in a group of participants for whom a traditional IPC stimulus was not effective, the magnification of the IPC stress through muscle contractions while under occlusion led to a subsequent exercise performance response. These findings support that amplification of the ischemic preconditioning stimulus augments the effect for exercise performance.